“His brain works in a different way”: siblings’ understanding of autism - Fjermestad, Krister W.; Lervik, Nora Hjelde (Frontiers in Psychiatry, 2025)
Siblings of autistic children are at increased risk of mental health problems. Lack of autism knowledge may contribute to this risk. We examined siblings’ autism knowledge using the Sibling Knowledge Interview (SKI) conducted by clinicians before a sibling intervention. The sample comprised 28 siblings (61% boys; 39% girls) aged 8 to 12 years. All had a brother or sister with a clinically confirmed autism diagnosis. Audiotaped recordings of the interviews were transcribed and analyzed thematically. We identified six main themes: (1) definition, including diagnostic label, localization, explanation, and etiology, (2) regulation-, behavior-, social-, and cognition-related challenges, (3) strengths, (4) health service and family-based interventions, (5) misconceptions, and (6) lack of knowledge. Siblings displayed some knowledge about the key aspects of autism but also expressed insecurity, lack of knowledge, confusion, and misconceptions. Siblings displayed a narrow vocabulary to describe their brother’s or sister’s autism diagnosis. Few siblings provided elaborate and rich answers. Several siblings provided vague descriptions. The youngest siblings had particularly few verbally rich answers and displayed limited knowledge. The findings indicate that siblings need more knowledge about their brother’s or sister’s autism diagnosis. Research is needed on how this information should be provided.